Reconstructing Marriage Agreements in Islamic Family Law: An Integrative Analysis of Fiqh, Maqāṣid al-Syari'ah, and Indonesian Positive Law - Lenny Guspidawati; Jumni Nelli (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study examines the reconstruction of the marriage agreement concept within Islamic family law by integrating classical–contemporary fiqh perspectives, the framework of maqāṣid al-sharī‘ah, and Indonesian positive law. Although marriage agreements have been widely discussed, previous studies tend to be fragmented and rarely combine these three analytical dimensions. Using a normative legal research method supported by conceptual, historical, and statutory approaches, this research finds that marriage agreements possess strong legitimacy within the Islamic legal tradition, grounded in the principles of al-maslahah, contractual stipulations (al-syurūṭ fī al-‘uqūd), and the inherent flexibility of mu‘āmalah. The maqāṣid al-sharī‘ah approach reveals that marriage agreements significantly contribute to the preservation of the five essential objectives of Islamic law: ḥifẓ al-māl, ḥifẓ al-nasl, ḥifẓ al-nafs, ḥifẓ al-‘aql, and ḥifẓ al-dīn. In the context of Indonesian positive law, Constitutional Court Decision No. 69/PUU-XIII/2015 expands the legal framework by allowing marriage agreements to be made after the marriage ceremony, reflecting a more progressive and responsive legal paradigm. This study concludes that an integrative reconstruction of marriage agreements can enhance stability, justice, and protection within Muslim families in Indonesia, and offers a substantial contribution to the development of family law reforms aligned with contemporary social dynamics